Crime and colonisation in Australia's Torres Strait Islands. Issue 1 (March 2020) - Staines, Zoe; Scott, John
The overrepresentation of Indigenous Australians in the criminal justice system has been thoroughly documented over a number of decades. However, studies tend to adopt homogenising discourses that fail to acknowledge or deeply examine the diversity of Indigenous Australian experiences of crime, including across geographic and cultural contexts. This has prompted calls for a more thorough investigation of how experiences of crime differ across Australia's Indigenous communities, including between remote Aboriginal and Torres Strait Islander communities. This paper forms part of a larger study, examining crime and justice in the Torres Strait Region, situated off the far northern tip of the State of Queensland. Here, we examine and compare reported crime trends in the Torres Straits with those in Queensland's remote Aboriginal communities and Queensland State on the whole. We then draw upon existing anthropological, historical and other literature to explore possible explanations for differences in these crime rates. We find that crime rates are generally lower in the Torres Strait Region and that the different historical experiences of colonisation and policing may provide a partial explanation for this, particularly through the lens of social disorganisation theory.